Simulasi Penyusunan Indeks Pertumbuhan Ekonomi Berkualitas - Hermada Dekiawan; Ronowati Tjandra; Budi Asmarawati; Hasan Subagyo (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
This study aims to analyze the quality of economic growth in the Solo Raya, which includes Surakarta, Boyolali, Sragen, Wonogiri, Klaten, Sukoharjo, and Karanganyar and compile a simulation of a composite index of quality economic growth. Quality economic growth is an important aspect in national and regional development. The definition of quality economic growth in this study is economic growth followed by an increase in the welfare aspect of society through the fundamental dimension, social dimension, and welfare dimension. Each dimension has several relevant indicators. To compare the quality of economic growth between regions in Solo Raya, each dimension will be compiled into a composite index after going through the normalization and weighting process. This index was developed from the Mlachila, Tapsoba, and Tapsoba (2014) models. Using 2010-2017 data as a simulation, the results show that Wonogiri Regency has the lowest rank while Sukoharjo Regency has the highest rank and Surakarta has second best rank.